The effect of negative incentives on job stability – An applied study on Saudi Post in the Asir region – - Zureik, Ali Yahya; Abu Al-Sondos, Ibrahim Abdulhamid Salama (Journal of Economic, Administrative and Legal Sciences, 2020)
The objectives of the study are to identify the reality of the implementation of negative incentives and studying the effect of negative incentives in achieving the stability of workers, in addition, to determine the differences in the level of job stability as a result of different demographic variables of the employees of the Saudi Postal Sector in Asir. The study’s hypothesis is that there is a high-level implementation of negative incentives in Saudi Post sector, as well as the existence of a statistically significant effect of negative incentives on job stability. In addition, there are significant differences in the level of job stability due to differences in the demographic variables in the Saudi Post Sector in Asir Region. The study population in Saudi Postal Sector, Asir Region, attain to (263) employees, which (95) chosen from the study community, including directors and heads of departments and staff and technicians, of which 5 questionnaires are invalid, the analytical descriptive approach and SPSS were used. The researcher used the descriptive-analytical method. Also prepared the questionnaire, which confirmed its validity and the stability by arbitrating by number of arbitrators. As well as to ensure stability, where the coefficient of stability (0.90). The results of the research show that there are statistically significant differences in the negative incentive practices which account for (72%) of the overall performance variance, also there are statistically significant differences at the level of 0.00 and lower among the attitudes of the study personnel working in the Saudi Postal Sector in Asir region. The most important recommendations are to continue and follow the policy of maintaining the high level of negative incentive practices in the Saudi postal sector in Asir.
Keywords: negative incentives; job stability